The impact of industrial production growth on regional development in Hungary, 2009–2021 - Lőrinc, Balázs; Káposzta, József (Studia Mundi – Economica, 2023)
The economic visions of the 1990s foresaw a number of trends for the 21st century that have generated significant changes. These changes were motivated by two major overarching factors: the vision of a knowledge society and the vision of a knowledge economy. The articulation of both factors has had such an impact on the development of education that we are witnessing the generation of continuous innovation trends. Taking a broad view of global trends, we can observe the erosion of competitiveness, increasing foreign competition, the overall effects of globalisation and liberalisation, the need to seek higher value-added and value-creating products and services, the need to move to more profitable and welfare-enhancing stages of production, the search for new sources of growth, the challenge of increasing total factor productivity, and the shift from an input-driven strategy to a productivity-driven strategy. In our study, we sought to answer the question of whether the increase in the value of industrial production has changed the spatial inequalities of production, and how the level and uneven spatial distribution of foreign direct investment affect the development of a given economic space in Hungary.
Keywords: regional economics; industrial production; Hoover-index